The Adhesion‐Enhanced Contact Electrification and Efficiency of Triboelectric Nanogenerators. Issue 1 (18th November 2019) - Lapčinskis, Linards; Mālnieks, Kaspars; Blūms, Juris; Knite, Māris; Oras, Sven; Käämbre, Tanel; Vlassov, Sergei; Antsov, Mikk; Timusk, Martin; Šutka, Andris
Abstract: In the present work, the contact electrification of polymers that differ in adhesion strength is studied. Electrical current is measured along with adhesion in macroscale contacting‐separation experiments. Additionally, local adhesion and roughness are studied with atomic force microscopy to get deeper insight into relations between surface properties and electrification. Measurements reveal that higher surface charge is formed on more adhesive surfaces, thus confirming covalent bond cleavage as a mechanism for contact electrification of polymers. Investigated materials possess enhanced contact electrification making them attractive candidates for the conversion of mechanical energy to electrical in triboelectric nanogenerator devices. Abstract : Heterolysis and mass transfer are confirmed by XPS and AFM as the primary mechanism for contact electrification of polymers as suggested by an evident correlation between adhesion and charge density. A new look is proposed on the calculation of TENG efficiency—one that takes into account separation forces.